2023
DOI: 10.3389/fclim.2023.1069514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of climate and non-climatic parameters on cocoa production: a contextual analysis for Cameroon

Abstract: Agriculture remains the mainstay of Cameroon's economy, with cocoa as one of its key export commodities. However, cocoa production may be affected by climate-related stressors. This study assesses the influence of climate and non-climate parameters on cocoa performance in Cameroon. We use time series data for temperature, rainfall, carbon dioxide emission, land use, labour hours, pesticide application, and cocoa output in Cameroon spanning 60 years (1961 to 2021). Trend analyses reveal a stochastic response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Some studies have rather evaluated the direct impact on crop production and they show varying impacts. For example, a study by Bomdzele and Molua (2023) show that climate change affects cocoa production while other studies have shown that it affects food crop production as well (Ngondjeb, 2013;Sotamenou and Saleu, 2013;Defang et al, 2014). This study provides additional empirical evidence on the impact of climate change on farm revenue in Cameroon.…”
Section: Agriculture and Climate Change In Cameroonmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have rather evaluated the direct impact on crop production and they show varying impacts. For example, a study by Bomdzele and Molua (2023) show that climate change affects cocoa production while other studies have shown that it affects food crop production as well (Ngondjeb, 2013;Sotamenou and Saleu, 2013;Defang et al, 2014). This study provides additional empirical evidence on the impact of climate change on farm revenue in Cameroon.…”
Section: Agriculture and Climate Change In Cameroonmentioning
confidence: 99%
“…To our knowledge, only the studies by Molua, (2009Molua, ( , 2022 have evaluated the effect of climate change on farm income in Cameroon. This is surprising given that Cameroon like most developing countries is already exposed to climate change and its impacts (Molua et al, 2010Molua, 2022;Bomdzele and Molua, 2023;Ngaiwi et al, 2023). Other studies from Cameroon have largely focused on adaptation strategies of farmers (Bele et al, 2011;Awazi et al, 2022;Ngaiwi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that African economies (especially low-income producers and consumers) are expected to bear the brunt of these changes due to their limited resources for investing in adaptation and diversification measures (Bailey et al, 2015;Bomdzele & Molua, 2023; Intergovernmental Panel on Climate Change [IPCC], 2014; UNCCD, 2017). It has been acknowledged that smallholder farming systems are exceptionally susceptible to the impacts of climate change (Morton, 2007).…”
Section: Climate Change Food Safety Nutrition and Health Outcomes Nexusmentioning
confidence: 99%